A new approach for determination of Na,K-ATPase activity: application to intact pancreatic ß-cells - Costa, Ana R. (2012)
It has been postulated that a decrease in Na,KATPase-mediated ion gradients may be a contributing mechanism to insulin secretion. However, the precise role of the Na,K-ATPase in pancreatic β-cell membrane depolarization and insulin secretion signalling have been difficult to evaluate, mostly because data reporting changes in enzymatic activity have been obtained in cell homogenates or membrane preparations, lacking intact intracellular signalling pathways. The aim of this work was to develop a method to characterize Na,K-ATPase activity in intact pancreatic β-cells that will allow the investigation of putative Na,K-ATPase activity regulation by glucose and its possible role in insulin secretion signalling. This work demonstrates for the first time that it is possible to determine Na,K-ATPase activity in intact pancreatic βcells and that this is a suitable method for the study of the mechanisms involved in the Na,K-ATPase regulation and eventually its relevance for insulin secretion signalling.